Ideal patients for liver resection in Barcelona Clinic Liver Cancer or Hong Kong Liver clinic systems for hepatocellular carcinoma: conservative or aggressive? - Li, Jun-Xiang; Zhou, Peng; Chang, De-Hua; Tong, Yao; Bao, Yan; Xiao, Yu-Dong; Zhou, Shi; Cai, Wen-Wu (Frontiers in medicine, 2022)
BackgroundBoth the Barcelona Clinic Liver Cancer (BCLC) staging and the Hong Kong Liver Cancer (HKLC) staging have their own definitions of ideal patients for liver resection (IPLR) in hepatocellular carcinoma (HCC). This study aimed to compare the prognosis of IPLRs between the BCLC and HKLC staging systems, and to identify patients who may benefit from liver resection (LR) in the HKLC staging but beyond the BCLC staging.MethodsThis retrospective study evaluated 1,296 consecutive patients with HCC who underwent LR between August 2013 and April 2021 (457 patients and 1,046 patients were IPLR according to the BCLC and HKLC staging systems, respectively). Overall survival (OS) was compared between the two groups. To assess potential benefit of LR for IPLR in the HKLC staging but beyond the BCLC staging, univariate and multivariate Cox regression analysis was performed to determine prognostic factors of OS, and prognostic stratification was performed based on the selected prognostic factors. The IPLRs in the HKLC staging but beyond the BCLC staging were divided into subgroups according to the prognostic stratification and separately compared with the IPLRs in the BCLC staging.ResultsOS was different between the two staging systems (P = 0.011). All the 457 IPLRs in the BCLC staging were also the IPLRs in the HKLC staging. Diameter of the largest tumor5 cm (HR = 1.58; 95% CI: 1.18-2.10; P = 0.002) and liver cirrhosis (HR = 1.61; 95% CI: 1.19-2.20; P = 0.002) were risk factors for poor OS in IPLRs in the HKLC staging but beyond the BCLC staging; hence, patients were divided into the low-risk (n = 104), intermediate-risk (n = 369), and high-risk groups (n = 116) accordingly. There was no difference in OS between patients in the BCLC staging and patients in low-risk group (P = 0.996). However, OS was significantly different between patients in the BCLC staging and those in intermediate-risk (P = 0.003) and high-risk groups (P < 0.001).ConclusionIPLRs in the BCLC staging system have better prognosis. However, IPLRs in the HKLC staging system but beyond the BCLC staging may have equivalent prognosis to IPLRs in the BCLC staging if the tumor size is ≤ 5 cm and liver cirrhosis is absent.
Gesehen am 09.12.2022